2017
DOI: 10.3389/fnins.2017.00700
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Ameliorates Blood-Brain Barrier Impairment Secondary to Ischemic Stroke via the Activation of PI3K Pathway

Abstract: Secondary impairment of blood-brain barrier (BBB) occurs in the remote thalamus after ischemic stroke. Netrin-1, an axonal guidance molecule, presents bifunctional effects on blood vessels through receptor-dependent pathways. This study investigates whether netrin-1 protects BBB against secondary injury. Netrin-1 (600 ng/d for 7 days) was intracerebroventricularly infused 24 h after middle cerebral artery occlusion (MCAO) in hypertensive rats. Neurological function was assessed 8 and 14 days after MCAO, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…In other studies, albumin staining in the ipsilesional thalamus has revealed changes in BBB permeability (50,69). Increased albumin extravasation and decreased tight-junction protein expression, such as zona occludin 1 (ZO-1) and occludin are shown in the ipsilesional thalamus as early as 24 h after cortical stroke, and persist through Day 14 after cortical stroke (50,69). Aberrant angiogenesis resulting in a loss of BBB integrity may contribute to inflammatory responses and injuries in the thalamus after cortical stroke.…”
Section: Bbb Breakdownmentioning
confidence: 99%
See 4 more Smart Citations
“…In other studies, albumin staining in the ipsilesional thalamus has revealed changes in BBB permeability (50,69). Increased albumin extravasation and decreased tight-junction protein expression, such as zona occludin 1 (ZO-1) and occludin are shown in the ipsilesional thalamus as early as 24 h after cortical stroke, and persist through Day 14 after cortical stroke (50,69). Aberrant angiogenesis resulting in a loss of BBB integrity may contribute to inflammatory responses and injuries in the thalamus after cortical stroke.…”
Section: Bbb Breakdownmentioning
confidence: 99%
“…Emerging studies have shown multiple pathological changes associated with the secondary thalamic degenerative injury after cortical ischemic stroke, including excitotoxicity (17,30), apoptosis (27,49), Aβ accumulation, BBB breakdown (50), and inflammatory responses (5,25). We will discuss them in detail in the following sections.…”
Section: Pathological Changes In Secondary Thalamic Injurymentioning
confidence: 99%
See 3 more Smart Citations